2008
DOI: 10.3171/spi-08/01/030
|View full text |Cite
|
Sign up to set email alerts
|

A long-term follow-up study of anterior tibial allografting and instrumentation in the management of thoracolumbar tuberculous spondylitis

Abstract: Object The purpose of this study was to determine the efficacy of anterior instrumentation following radical debridement and tibial allografting and its long-term progression in patients with multilevel spinal tuberculosis. Methods This prospective observational study was undertaken to analyze 22 patients with multilevel spinal tuberculosis (Pott disease) who underwent anterior radical debridement, decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 38 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Cavuşoğlu et al [112] reported long-term results on anterior radical debridement, decompression, and fusion using anterior spinal instrumentation and tibial allograft replacement for management of multilevel spinal TB in 22 patients. Their findings revealed that this technique provides correction of the curvature, prevents further deformation, improves sagittal and coronal balance, and restores neurological function.…”
Section: Multiple Vertebral Diseasementioning
confidence: 99%
“…Cavuşoğlu et al [112] reported long-term results on anterior radical debridement, decompression, and fusion using anterior spinal instrumentation and tibial allograft replacement for management of multilevel spinal TB in 22 patients. Their findings revealed that this technique provides correction of the curvature, prevents further deformation, improves sagittal and coronal balance, and restores neurological function.…”
Section: Multiple Vertebral Diseasementioning
confidence: 99%
“…Additionally, it can be the most dangerous form of skeletal TB due to its capacity for causing bone destruction, deformity and paraplegia (5). Anti-tuberculous chemotherapy has proven effective in the majority of cases and has become the mainstay of treatment (6), yet it cannot prevent kyphotic degeneration (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…88 percent of patients achieved solid bony fusion on average 6.3 months postoperatively. Most series report solid bony fusion to occur in over 90 percent of cases [11,13,30,38] and time to fusion from 7.5 to 8.6 months [30,38,39]. Kyphosis correction averaged 8 degrees in present series as compared to 12.5 degrees in other series [21].…”
Section: Discussionmentioning
confidence: 64%